Projeto robusto de Circuitos Shunt para o controle passivo de vibrações de estruturas compostas - Vicente, Bruno Gabriel Gustavo Leonardo Zambolini (2014)
This work focuses on the finite element modeling procedure and the robust-optimal design of composite structures containing piezoelectric elements to be coupled with the so-named shunt circuits with the aim of passive vibration attenuation. The work is organized into two main parts as follows: the first is devoted to the use of the first order shear deformation theory (FSDT) in conjunction with the single equivalent layer theory for the modeling of the mechanical problem composed by a thin rectangular composite plate structure. At this step, the mixed theory, in which the single layer equivalent theory is combined with the discrete theory to model electromechanical system (composite structure with piezoelectric elements), is also employed. Emphasis is also placed on the parameterization strategy of the design variables such as the layer s thicknesses, the directions of the fibers and the parameters of the shunt circuits. It must be emphasized that the finite element models were developed and implemented in MATLAB® environment; the second part of the work is dedicated to the quantification of the parametric uncertainties related to the resistance and inductance of the resonant shunt circuit and the thickness of the piezoelectric element. In order to create the probabilistic models the Maximum Entropy Method (MME) is retained and the resulting stochastic model is solved by using the so-called Monte Carlo method. The interest is to generate the limits of dispersion and the number of random simulations required to be used in the robust multi-objective optimization process of the shunt circuits by taking into account during the simulations the vulnerability functions to be optimized at the same time as the original objective functions.